The development of a solid-phase fermentation system for the production of pharmaceutically useful secondary metabolites in fungi - Aldred, David (Cranfield University, 2000)
A Phoma species, producing a squalestatin (Si) was grown on agar media derived from wheat, oats, oil seed rape and malt extract over a range of water availability values corresponding to water activity (aa) levels of. 0.998,0.995,0.990,0.980 and 0.960. Growth of the organism was not significantly affected by aw, except at the lowest value, but production of SI was significantly enhanced at intermediate aW in the range 0.990 - 0.980. For example, at 25°C and 0.98 aw wheat extract produced a l Ox increase in titre compared to 0.998 aw at the same temperature. Wheat extract was shown to be the best substrate for SI production. For example, at 25°C and 0.98 aW, this substrate produced 2x, 5x and 8x increases in titres compared to oat, malt and oil seed rape extracts respectively. A range of raw and processed agricultural products, including those used as extracts with the Phoma species, as well as maize, rice, soya, wheat flakes, bulgar wheat, couscous and "shredded wheat", were selected as candidate materials for solid substrate fermentation (SSF). Moisture sorption isotherms were prepared for each of these so that aW could be accurately set in experimental work. Small scale fermentations (40 cm3 wet substrate volume) were carried out with these materials and the fungi Epicoccum nigrum, Sarophorum palmicola, Drechslera dematioidea and Corynespora cassiicola over the aw range 0.998 - 0.970. Studies with E. nigrum in particular produced a range of unique metabolites at low aw, and other metabolites where titres were increased by as much as 20x compared to high aW conditions. The optimum aw level for metabolite production in this fungus appeared to be in the range 0.990-0.980. Ultimately, E. nigrum was chosen as the model fungus and bulgar wheat as the model substrate, with 3 key target metabolites being followed (metabolites 1,2 and 3). A series of scale-up studies (40 cm3-3 litres wet volume) were carried out utilising the model system. These studies typically produced reasonable levels of metabolites, but were subject to problematic water and heat accumulation, and bacterial contamination. These were identified as critical parameters. A system was ultimately developed around a Bioengineering AG submerged liquid fermenter, modified for use with solid substrates, and incorporating forced aeration and mechanical agitation. This apparatus gave encouraging levels of metabolites, producing most of these rapidly and uniformly, and showed good critical parameter control. The overall scale-up achieved in the final fermenter studies was 75x, in terms of wet substrate volume. Increased titres were achieved for all three target metabolites compared to small-scale studies with the same substrate. These increases were approx. 17x for metabolite 1, approx. 3x for metabolite 3, while metabolite 2 was absent from small scale studies at the relevant aW level.